2023
DOI: 10.1111/gcb.16574
|View full text |Cite
|
Sign up to set email alerts
|

Global net biome CO2exchange predicted comparably well using parameter–environment relationships and plant functional types

Abstract: Despite their importance for understanding the role of terrestrial ecosystems in a changing climate, forecasts of net biome CO2 exchange are hindered by uncertainty in model parameters. Here, we compare the traditional plant functional type (PFT)-based parameterization approach to a novel top-down, machine learning-based "environmental filtering" (EF) approach.We find that the EF-based approach matches or outperforms the PFT-based approach at a narrow majority of vegetated pixels across the globe. KEYWORDSThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…(2022) found PFTs to exhibit strong control on spatial variation of peatland fluxes, while a PFT approach for modeling global fluxes produced similar results to a more complicated ”environmental filtering” framework in a study by Famiglietti et al. (2023).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…(2022) found PFTs to exhibit strong control on spatial variation of peatland fluxes, while a PFT approach for modeling global fluxes produced similar results to a more complicated ”environmental filtering” framework in a study by Famiglietti et al. (2023).…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, recent studies have not necessarily produced results consistent with PFTs being fully obsolete (Thomas et al, 2019). Laine et al (2022) found PFTs to exhibit strong control on spatial variation of peatland fluxes, while a PFT approach for modeling global fluxes produced similar results to a more complicated "environmental filtering" framework in a study by Famiglietti et al (2023).…”
mentioning
confidence: 92%
“…The strong relationship between τ and D max (Figure 4) also motivates the parametrization of stomatal closure in models as a function of local climate, not just using plant functional types, as is commonly done. This approach is known as environmental filtering (e.g., Famiglietti et al., 2023; Walker et al., 2017). Our findings are consistent with previous findings of instantaneous stomatal parameters being related to aridity (Bassiouni et al., 2023; Lin et al., 2015; Y. Liu et al., 2022) and rainfall intensity and frequency (Bassiouni et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Madani et al, 2018) and inform trait-based modeling efforts across scales (e.g. Famiglietti et al, 2023). Fig.…”
Section: Conclusion and Paths Forwardmentioning
confidence: 99%
“…While such relationships have myriad applications in trait-based ecology, including flexibly parameterizing large-scale ecological models (e.g. Verheijen et al, 2013Verheijen et al, , 2015Famiglietti et al, 2023), as well as extrapolating between sparse in situ data (Borgy et al, 2017), their potential utility is hampered by their relatively low predictability (Anderegg, 2023).…”
Section: Introductionmentioning
confidence: 99%